The relationship between GPs and hospital consultants and the implications for patient care: a qualitative study. Issue 1 (December 2016) - Sampson, Rod; Barbour, Rosaline; Wilson, Philip
Abstract Background Improving the quality of care of at the medical primary-secondary care interface is both a national and a wider concern. In a qualitative exploration of clinicians' relationship at the interface, we want to study how both GPs and hospital specialists regard and behave towards each other and how this may influence patient care. Method A qualitative interview study was carried out in primary and secondary care centres in NHS Highland health board area, Scotland. Eligible clinicians (general practitioners and hospital specialists) were invited to take part in a semi-structured interview to explore the implications of interface relationships upon patient care. A standard thematic analysis was used, involving an iterative process based on grounded theory. Results Key themes that emerged for clinicians included communication (the importance of accessing and listening to one another, and the transfer of soft intelligence), conduct (referring to perceived inappropriate transfer of workload at the interface, and resistance to this transfer), relationships (between interface clinicians and between clinicians and their patients), and unrealistic expectations (clinicians expressing idealistic hopes of what their colleagues at the other interface could achieve). Conclusion The relationship between primary and secondary care clinicians, and, in particular, difficulties and misunderstandings can have an influence upon patient care. Addressing key areas identified in the study may help to improve interface relationships and benefit patient care.